Concordance of clinical, histopathologic and direct Immunofluorescence findings in patients with intraepidermal immunobullous disorders - Erum Ashraf,; Shareef, Faryal (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the concordance among clinical, histopathological and immunofluorescence as diagnostic methods for intraepidermal immunobullous disorders. Method: The prospective cross-sectional study was conducted at the Institute of Skin Diseases, Karachi, from December 2020 to December 2022, and comprised adult patients of either gender presenting with complaints of bullae, vesicles, pustules and crusts on the skin or mucous membrane. Diagnostic findings of each patient as obtained by clinical assessment, microscopy and direct immunofluorescence were compared. Data was analysed using SPSS 19. Results: Of the 81 patients, 41(50.6%) were males and 40(49.4%) were females. The overall median age was 35 years (interquartile range: 23 years), with 66(75%) patients aged 19-55 years. The predominant body site involved was the trunk 49(60.5%), followed by mucosa 26(32.1%). Clinical diagnosis detected 80(98.7%) cases, compared to 76(93.8%) by microscopy and 81(100%) by direct immunofluorescence. Conclusion: Direct immunofluorescence was found to be the gold standard for a confirmatory diagnosis of intraepidermal immunobullous disorders, especially when clinical and histopathology findings were inconclusive. Key Words: Intraepidermal immunobullous disorders, Pemphigus vulgaris, Histopathology, Direct immunofluorescence.